Islamic Boarding School Economic Institutions in the Perspective of Maslahah and Customer Satisfaction through Product Completeness - Siswadi; Anas Al Hifni; Biyati Ahwarumi; Muhamad Malik Azhar (Universitas Wahid Hasyim Semarang, 2026)
Islamic boarding schools (pesantren) have developed not only as educational institutions but also as socio-economic institutions that support community welfare through various economic activities. One of the emerging economic institutions is pesantren-based retail, which plays a strategic role in promoting economic self-reliance while embodying Islamic values. This study aimed to analyze the role of pesantren economic institutions from the perspective of maslahah and customer satisfaction through product completeness at Mrican Tuban Department Store. This study employed a quantitative correlational design using convenience sampling Data were collected using a structured questionnaire with five-point Likert-scale items and analyzed using validity and reliability tests, descriptive statistics, and simple linear regression. The results show that product completeness has a positive and significant effect on customer satisfaction, with a coefficient of determination (R²) of 0.316, indicating that 31.6% of customer satisfaction is influenced by product completeness. From the perspective of Islamic economics, reflects the principle of maslahah by ccessibility, efficiency, and convenience in fulfilling daily needs. These findings confirm that managing pesantren retail based on product completeness not only enhances customer satisfaction but also strengthens the role of pesantren as an economic institution grounded in Islamic ethical and social values.